Evaluation study on performance of heat exchanger – 4000 in central processing area PT. PertaminA EP Asset 4 Sukowati Field - ERWAN ADI SAPUTRO (Machine : Jurnal Teknik Mesin, 2026)
PT Pertamina EP Asset 4 is one of Pertamina's subsidiaries operating in the oil and gas industry. In its production process, PT Pertamina EP Asset 4 requires heat exchangers for various purposes. Impurities on the shell and tube walls is unavoidable, which, if left unchecked, will disrupt the efficiency of the heat exchanger. These impurities accumulate over time and hinder the heat exchanger's efficiency due to debris adhering to the shell and tube surfaces. Therefore, this calculation is aimed at determining the heat transfer efficiency during industrial processes. Heat efficiency, which describes the ratio of heat transferred from a high-temperature fluid (water) to a low-temperature fluid (oil) per unit of time, is a crucial metric for evaluating the effectiveness of the heat exchanger. The research findings show that the overall net coefficient (Uc) and overall design average coefficient (Ud) are recorded at 88.2422 Btu/ft2.hr.°F and 51.7160 Btu/ft2.hr.°F, respectively. Meanwhile, the fouling factor (Rd) is assessed at 0.0079 ft2.hr°F/Btu. Based on the significant difference between Uc and Ud as well as the high Rd value, it can be concluded that the heat exchanger unit has experienced considerable fouling, necessitating a special mechanical cleaning to restore its performance.